Deregulation, competition, and market integration in China’s electricity sector - Wu, Y.; Guo, X.; Marinova, Dora (Routledge, 2017)
The Routledge Handbook of Energy in Asia presents a comprehensive review of the unprecedented growth of Asian energy over the past quarter of a century. It provides insightful analysis into variation across the continent, whilst highlighting areas of cross-learning and regional cooperation between the developed and developing countries of Asia. Prepared by a team of leading international experts , this book not only captures East Asian domination, particularly that of China, but also ...